Observasi Histologik dan Identifikasi Fungi Endofit yang Diisolasi dari Cananga odorata (Lam.) Hook.F. & Thomson - Hastuti, Utami Sri; Rakhmawati, Dwi; Sari, Ria Yustika (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Some endophytic fungi live in medicinal plant tissue, include medicinal plant. This research was done to: 1) determine the endophytic fungi position in the Cananga odorata plant tissue by histological observation; 2) identify the endophytic fungi species isolated from the leaf, twig, and petal flower of C. odorata. The position determination of endophytic fungi in the C. odorata plant tissue is done by microscopic observation. The endophytic fungi were isolated from the leaf, twig, and flower petal of C. odorata plant by cutted these plant parts, then inoculated on Potato Dextrose Agar (PDA) medium and incubated in 27oC during 7 x 24 hours, each fungi that grow on the PDA medium were isolated, then the morphology and microscopic characteristic of each fungi colony isolates were described. Each endophytic fungi isolates were identified. The research result were: 1) the endophytic fungi position are on the epidermis cell wall and on the stomata guard cell wallof the leaf tissue, on the parenchymal cell wall of the twig tissue, and on the epidermis cell wall of the flower tissue; 2) Nine endophytic fungi species were isolated from the C. odorata leaf, twig, and flower petal are: Nigrospora sphaerica, Colletotrichum alienum,Mycellia sterilia1, C. kahawae, Rhizoctonia sp., C. aotearoa, Micellia sterilia2, C. alatae, dan C. queenslandicum